A scoping review of initiatives to reduce inappropriate or non-beneficial hospital admissions and bed days in people nearing the end of their life: much innovation, but limited supporting evidence - Wee, B; Taylor, R; Ellis, J; Gao, W; Searle, L; Heaps, K; Davies, R; Hawkesworth, C; Garcia-Perez, A; Colclough, G; Walker, S (BioMed Central, 2020)
Background: Hospitalisation during the last weeks of life when there is no medical need or desire to be there is distressing and expensive. This study sought palliative care initiatives which may avoid or shorten hospital stay at the end of life and analysed their success in terms reducing bed days.